Iptek bagi Masyarakat (IbM) Kelompok Petani Ikan Kelurahan Rap Rap - Kalesaran, Ockstan J.; Lantu, Sartje (Universitas Sam Ratulangi, 2016)
The implementation of science and technology for society aimed to give knowledge and methods of application that can answer all problems encountered by fish farmers. Low cost of Â feed manufacturing methods and high quality utilizing local raw ingredients had been given through counseling and basic training so that fish farmers can continue going forward and do not rely on commercial feed from the market.Â Practical sex reversal methods were given, intended that fish farmers could get male tilapia seeds having rapid growth. Â Keywords: Fish farmer, Rap Rap Village, feed, eeed, Sex Reversal Methods